Characterization and experimental investigation of aluminum nitride-based composite phase change materials for battery thermal management. (15th January 2020) - Zhang, Jiangyun; Li, Xinxi; Zhang, Guoqing; Wang, Yongzhen; Guo, Jianwei; Wang, Ye; Huang, Qiqiu; Xiao, Changren; Zhong, Zhaoda
Highlights: A novel aluminum nitride-enhanced composite phase change material is proposed. Aluminum nitride enhance thermal conductivity and stability of composite materials. Aluminum nitride increase volume resistivity and mechanical strength of materials. Composite phase change material display excellent battery thermal management effect. Abstract: Thermal management plays an important role in battery modules, especially under extreme operating conditions. Phase change materials (PCMs)-based cooling has been recognized as a promising approach that can prolong the life span of batteries and endure the passive thermal accumulation in the module. In this study, various mass fractions (0 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, and 25 wt%) of aluminum nitride (AlN) were added to composite PCMs to serve as heat-transfer promoters. The effect of the AlN additives on the thermal conductivity, mechanical properties, and volume resistivity were analyzed, and the root causes originating from the morphologies and structures of the composite PCMs were further examined. The results indicated that adding 20 wt% of the AlN in the composite PCMs was an optimal strategy. In addition, an AlN/paraffin (PA)/expanded graphite (EG)/epoxy resin composite PCMs-based 18650 LiFePO4 battery module was designed for thermal management. This battery module exhibited much better heat dissipation and temperature uniformity than an air-cooled battery module, leading to a 19.4% decrease of the maximum temperature and a less than 1 °C temperature difference at a high discharge rate of 3C. Thus, it could be concluded that the AlN-enhanced composite PCMs thermal management system exhibited a prominent controlling temperature and balancing temperature capacity for the battery module.